Maths pro (I) - Teo, Yu Quan (2015)
In 2005, the Singapore Government spearheaded an initiative called the Intelligent Nation 2015 (iN2015), which is a 10 year masterplan to grow the Infocommunication industry and also to make use of Infocommunication technology (IT) to enhance and build a well-connected society. One of the main aims of the iN2015 is to empower learners, letting each and every individual to make use of IT to learn at their pace, time and place. Learning should not stop at just the school or classroom level, but beyond that. By making use of IT we can dwell into the realm of Internet, which provides the perfect medium for learning to continuously take place. Though student may be learning at their own pace, instructor will still be able to monitor the progress of the student. This form of online learning sort of give a ‘one to one’ interactive kind of personalized teaching, rather than the ‘one to many’ form of teaching carried out in schools. With this, the education system in Singapore can be taken to a whole new level, whereby learning can take place practically 24/7. Hence with this in mind, this online web based learning portal project; Maths Pro will be in line with the iN2015. Created using Hypertext Markup Language (HTML), Cascading Style Sheets (CSS), JavaScript, Hypertext Preprocessor (PHP) and Structured Query Language (SQL), we are able to simulate a virtual classroom, which allows learning to take place anytime and anyplace. From the viewing of each and every student’s statistics, instructors will be able to closely monitor their progress at the same time. In this independent learning environment, by employing the usage of online lectures, tutorials, quizzes and materials sharing, it will be result in a very different experience for both students and instructors as the whole process of learning and teaching is made more simple and convenient. It is also likely to enhance the learning and understanding of every student in the topic of Engineering Mathematics (Numerical Method etc.).